Preliminary Validation of the Exercise-Snacking Licensing Scale: Rewarding Exercise with Unhealthy Snack Foods and Drinks - West, Jessica S. (Nutrients, 2018)
There is evidence that individuals’ compensatory health beliefs may be an important psychological driver of health behavior. Only recently, however, have researchers begun to develop and seek to validate instruments that are suited to measuring specific pairings of the diverse compensatory health beliefs that exist. The aim of this study was to provide support for key aspects of validity associated with the Exercise-Snacking Licensing Scale (ESLS), an instrument that was designed to assess individuals’ endorsement (or licensing) of unhealthy snacking behaviors around exercise. Participants (N = 1095) responded to a version of the ESLS that was designed to assess their licensing responses following either “light” or “tiring” physical activity, and completed additional instruments assessing dispositional, exercise-related, and diet-related constructs. Analyses indicated that scores derived from both versions of the ESLS (“light” and “tiring” physical activity) displayed a relatively consistent factor structure, favorable alpha coefficients, and meaningful correlations with variables that are theoretically aligned with licensing. Factor analytic procedures did, however, indicate that researchers may wish, in future, to consider the use (or not) of reverse-scored items within the ESLS. Together, these findings provide important insight into the structural, external, and generalizability aspects of validity for scores derived from the ESLS, and indicate that the ESLS may be a valuable instrument for the brief assessment of unhealthy licensing beliefs around exercise. Further use of the ESLS is encouraged to determine if and how these licensing beliefs actually influence subsequent snacking behaviors, and the potential downstream effects these beliefs may have in shaping health outcomes associated with exercise participation.